Statistical Exploration of State Land Use Policy in Scopus: A Bibliometric Perspective - Baginda Fida Akasa; Muhammad Subhi Apriantoro (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to map the development, research focus, and intellectual structure of State Land Use Policy studies through a bibliometric analysis of Scopus-indexed publications, with particular relevance for informing sustainable land use policy development in Indonesia. Methodology: A bibliometric method was employed using data retrieved from the Scopus database, covering publications from 2021 to 2024. The analysis examines publication trends, author productivity, institutional affiliations, contributing countries, and the frequency of key terms to identify dominant themes and research patterns in the field of land use policy. Results: The results indicate a growing trend in publications on state land use policy over recent years. Research is predominantly contributed by authors affiliated with leading universities in countries such as the United States, China, and the United Kingdom. Major research themes focus on land conflicts, sustainable land use, environmental impacts, and policy implications for society. Frequently occurring keywords include land use, land use policy, land conflict, sustainable agriculture, and land use planning, reflecting the core concerns of the literature. Applications/Originality/Value: This study offers a systematic overview of global research on state land use policy and highlights key thematic and geographical trends. It provides valuable insights for researchers, policymakers, and practitioners, particularly in Indonesia, by identifying dominant issues, leading contributors, and potential research gaps that can support the formulation of evidence-based and sustainable land use policies.